Nano-Tera.ch Engineering the Future of Systems for Health, Environment and Energy - Leblebici, Anil.; Mayor, Patrick; Rajman, Martin; De Micheli, Giovanni; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the overall vision and research outcomes of Nano-Tera.ch, which is a landmark Swiss federal program to advance engineering system and device technologies with applications to Health and the Environment, including smart Energy generation and consumption. The authors discuss this unprecedented nation-wide program, with a lifetime of almost 10 years and a public funding of more than 120 MCHF, which helped to position Switzerland at the forefront of the research on multi-scale engineering of complex systems and networks, and strongly impacted the Swiss landscape in Engineering Sciences. .
Introduction -- Output of selected research activities -- Impact of the program -- References and contributors -- Conclusions.
Keywords: Electronic circuits; Signal processing; Electronics; Electronic Circuits and Systems; Signal, Speech and Image Processing; Electronics and Microelectronics, Instrumentation